Palladium-Catalyzed Cross-Coupling between 7-Azaindoles and Reformatsky Reagents - Barl, Nadja M.; Malakhov, Vladimir; Mathes, Christian; Lustenberger, Philipp; Knochel, Paul (Synthesis, 2015)
The preparation of various 2-(7-azaindolyl)carboxylic esters by Pd-catalyzed coupling of Reformatsky reagents with TBDMS-protected 3-bromo-7-azaindoles leading to a wide range of arylated ester derivatives is reported. After removal of the protecting group, the corresponding free 2-(7-azaindolyl)carboxylic esters are obtained in satisfactory yields.
Keywords: azaindole; Reformatsky reagents; metalation; palladium; cross-coupling